To Be Supported, or Not to Be: Images of Older People in Policy and the Reality in Local Communities in Japan - Aoo, Ken; Abe, Noriko; Kano, Mitsunobu R. (Frontiers in Sociology, 2019)
Social innovation is not only about tangible new products, services, policies, and laws, but also about changes in societal perception, values, and norms. In Japan, current policies for older people, including Long-Term Care Insurance, have a tendency to focus on medical and long-term care, and other forms of "support" for the elderly such as pension. Naturally, these policies depict the elderly as the “beneficiaries,” or the ones who need support. However, when we look back at pre-modern Japan, it was not always like that. Although elderly people did depend on support from family and community members, they also had a role as an active laborer and caretaker, as well as providing useful knowledge for their family and community. And currently, in different areas suffering from population decline such as Okayama prefecture in western Japan as an example, older people are actually playing the role of the supporter for groups of people who are in need, not only the aged population but also other demographics including young children and parents. Based on this historic “tradition” and the present reality, this paper argues that we need to re-establish the image of (at least some) older people who take a more active and responsible role in society, and position them as such in the new “welfare society” systems in order to replace the conventional “welfare state” model.